Creating a health promotion university through healthy canteen development in a private university - Agustin, Helfi; Musfirah, Musfirah; Rahayu, Atikah (Intelektual Pustaka Media Utama, 2023)
A healthy canteen is one of the supporting elements of healthy campus infrastructure. Leaders' policies, engagement, and support are essential for healthy campus initiation advocacy initiatives. This qualitative case study approach aims to determine the possibility of implementing a healthy canteen in a private university. The study was conducted in Yogyakarta from July 2017 until March 2018 with informants sequentially from five university leaders, one canteen manager, ten canteen consumers, and including 15 food handlers. We collected data through in-depth interviews and then analyzed it with content analysis. Finally, we use the SWOT matrix to investigate the possibility of developing a healthy canteen at private colleges using strengths, weaknesses, opportunities, and threats. The obstacle to developing healthy canteens is the limited area for infrastructure. We found environmental health problems, such as unqualified sanitary conditions and unapplied food hygiene and sanitation principles. Healthy canteen could be developed if the leaders at all levels committed to allocating spaces and sanitation infrastructure, making policies and regulations for testing the food in laboratories, training and inspecting food handlers regularly and providing quality foodstuffs, clean and healthy nutritious food, and educating customers with posters on the canteen walls.